Learning through Activity: Women’s Work in History and Physical Activity in the Classroom - Ollilainen, Marjukka (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Women’s work in history This activity draws from students’ experiences with the goal of connecting their own lives to social phenomena, such as women’s labor force participation and social inequality.